The relation between the effects of testimonials' sources and the cognitive, affective and behavioural changes - Tudor Tocila; Corina Cara (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - Endorsement strategies have a well-known potential of generating good results and there are various studies which refer to the endorsement sources as either a contextually effective or ineffective strategy. The present study is a new approach on this topic and it aims at identifying whether there are significant attitude changes towards the service category after the exposure to different types of service brand testimonials or not. The service category is represented by cosmetic treatments. The attitude structure in this study specifies three distinct components: the affective, the behavioural and the cognitive one. Design/methodology/approach - The study was conducted on a sample of 426 males and females from Romania. Each subject was exposed to testimonials coming from experts, celebrities and satisfied customers who were endorsing a branded cosmetic treatment. Measurements included endorsers' perceived credibility and changes in affective, cognitive and behavioural attitudes towards the service category. Findings - Credibility derived from brand testimonials has an impact on the service category, as all three changes have been significant. The change in behavioural attitude was the most affected by perceived credibility, closely followed by the change in affective attitude and the change in cognitive attitude. Gender differences were also discussed. Research limitations/implications - The measurement of the endorsement's effect was performed only through the instrumentality of credibility. Another limitation is the survey context in which subjects got in contact with testimonials. Originality/value - This research is useful for both academics and practitioners, offering insights for those who are interested in attitude research and for those activating in the field of beauty service industry.
Keywords: M31; M37; 330; Testimonials; Affective; Behavioural; Cognitive; Attitudes